Habenula–ventral tegmental area functional coupling and risk aversion in humans - Wanjun Lin; Jiahua Xu; Xiaoying Zhang; Raymond J. Dolan (Proceedings of the National Academy of Sciences, 2025)
Maladaptive responses to uncertainty, including excessive risk seeking or avoidance, are linked to a range of mental disorders. One expression of these is a provariance bias (PVB), i.e., risk-seeking manifests as a preference for choosing options with higher variances/uncertainty. Using a magnitude learning task, we show that individual differences in PVB are explained by a model that includes asymmetric learning rates, allowing differential learning from positive prediction errors (PPEs) and negative prediction errors (NPEs). Using high-resolution 7T functional MRI (fMRI), we identify distinct neural responses to PPEs and NPEs in value-sensitive regions, including habenula (Hb), ventral tegmental area (VTA), nucleus accumbens (NAcc), and ventral medial prefrontal cortex (vmPFC) in humans. Notably, prediction error signals in NAcc and vmPFC were boosted for high variance options. NPEs responses in NAcc were associated with a negative bias in learning rates that was linked to the strength of Hb-VTA negative functional coupling during NPE encoding, with a mediation analysis revealing this coupling influenced NAcc responses to NPEs via an impact on learning rate bias. Our findings implicate Hb-VTA functional coupling in the emergence of risk preferences during learning, with implications for psychopathology.